Eficiência nos gastos públicos em educação fundamental: uma análise nos municípios do estado do Rio Grande do Norte, 2007 e 2011 - Dantas, Fabiano da Costa (2013)
This paper aims to measure the degree of efficiency in the allocation of public resources in education from the FUNDEB in elementary education in the towns of Rio Grande do Norte in 2007 and 2011. To do so, we must determine to evaluate the efficiency in the allocation of public resources in municipal education in the early and last grades of elementary education; verify that the towns that achieved higher levels of efficiency that were allocated the largest volumes of resources in primary education and analyze which towns reached the worst and the best levels of efficiency in the allocation of public resources in education. This is on the assumption that the relation between the educational policies of local governments and concern for efficiency in the allocation of resources in education is limited only to increase spending on education. It is intended from the model of Data Envelopment analysis, (DEA), with Variable Returns to Scale (VRS), estimate the efficiency of spending on education and municipal pubic purging the problem of outliers. Estimations show that the municipalities of Rio Grande do Norte do not allocate their resources in public elementary education efficiently